Cancer surveillance and distress among adult pathogenic TP53 germline variant carriers in Germany: A multicenter feasibility and acceptance survey. Issue 17 (18th June 2020) - Rippinger, Nathalie; Fischer, Christine; Haun, Markus W.; Rhiem, Kerstin; Grill, Sabine; Kiechle, Marion; Cremer, Friedrich W.; Kast, Karin; Nguyen, Huu P.; Ditsch, Nina; Kratz, Christian P.; Vogel, Julia; et al.
Abstract : Background: Li‐Fraumeni syndrome (LFS) is a high‐risk cancer predisposition syndrome caused by pathogenic germline variants of TP53 . Cancer surveillance has noted a significant survival advantage in individuals with LFS; however, little is known about the feasibility, acceptance, and psychosocial effects of such a program. Methods: Pathogenic TP53 germline variant carriers completed a 7‐part questionnaire evaluating sociodemographics, cancer history, surveillance participation, reasons for nonadherence, worries, and distress adapted from the Cancer Worry Scale. Counselees' common concerns and suggestions were assessed in MAXQDA Analytics Pro 12. Results: Forty‐nine participants (46 females and 3 males), aged 40.0 ± 12.6 years, formed the study population; 43 (88%) had a personal cancer history (including multiple cancers in 10 [20%]). Forty‐three individuals participated (88%) in surveillance during the study or formerly. Willingness to undergo surveillance was influenced by satisfaction with genetic testing and counseling ( P  = .019 [Fisher‐Yates test]) but not by sociodemographics, cancer history, or distress level. Almost one‐third of the participants reported logistical difficulties in implementing surveillance because of the high frequency of medical visits, scheduling difficulties, and the travel distance to their surveillance providers. Self‐reported distress and perceived emotional burden for family members and partners were moderate (median for self‐reported distress, 3.3; median for perceived emotional burden, 3.0). For both, the interquartile range was moderate to very high (2.7‐3.7 and 3.0‐3.7, respectively). Conclusions: Individuals with LFS require efficient counseling as well as an accessible, well‐organized, interdisciplinary, standardized surveillance program to increase adherence and psychological coping. Abstract : Individuals with Li‐Fraumeni syndrome face challenging surveillance protocols. Organizational problems and worries about family members, particularly children, are omnipresent in this population.